Agri-food supply chain coordination: the state-of-the-art and recent developments - Yuanita Handayati; Togar M. Simatupang; Tomy Perdana (Logistics Research, 2015)
Researches on agri-food supply chain coordination have been gaining public attention due to their critical relevance to food availability, security, and safety. Still, the research focus is considerably in its early stage of development. This study was aimed at reviewing a holistic understanding on agri-food supply chain, particularly on issues related to coordination. This review was conducted by analyzing selected articles from peer-reviewed journals and proceedings. The articles are classified based on three important categories for researches on agri-food supply chain coordination, i.e., interdependencies, coordination mechanism, and methodology. Based on an analysis on the current state of research, a future research on agri-food supply chain coordination should be encouraged. Besides, the spectrum of coordination mechanism taken to deal with different levels of interdependencies and quality requirements is presented. The spectrum is useful for any member in an agriculture supply chain who is willing to coordinate its actions with other members for improving supply chain performance. Then, the results of analysis suggest that a further research on the adoption of value co-creation in the coordination process is required to deliver benefits not only for participating actors but also for end consumers.
Keywords: 650; Supply chain; Coordination; Agriculture; Fruits and vegetables; Literature review